A secure data outsourcing scheme based on Asmuth–Bloom secret sharing. Issue 9 (21st November 2016) - Muhammad, Yusuf Idris; Kaiiali, Mustafa; Habbal, Adib; Wazan, A. S.; Sani Ilyasu, Auwal
ABSTRACT: Data outsourcing is an emerging paradigm for data management in which a database is provided as a service by third-party service providers. One of the major benefits of offering database as a service is to provide organisations, which are unable to purchase expensive hardware and software to host their databases, with efficient data storage accessible online at a cheap rate. Despite that, several issues of data confidentiality, integrity, availability and efficient indexing of users' queries at the server side have to be addressed in the data outsourcing paradigm. Service providers have to guarantee that their clients' data are secured against internal (insider) and external attacks. This paper briefly analyses the existing indexing schemes in data outsourcing and highlights their advantages and disadvantages. Then, this paper proposes a secure data outsourcing scheme based on Asmuth–Bloom secret sharing which tries to address the issues in data outsourcing such as data confidentiality, availability and order preservation for efficient indexing.